PRECONDITIONS OF FORMATION OF THE COMPETITIVE ENVIRONMENT OF THE REGIONAL REPRODUCTION PROCESS - K. M. Urusova; I. N. Urusova (Russian Journal of Economics and Law)
The article considers the factor and the structural features of the competitive environment of the reproduction process in the region.